2016 Thunderstorm-asthma epidemic in Melbourne, Australia: An analysis of patient characteristics associated with hospitalization. Issue 5 (22nd October 2021) - Harun, Nur-Shirin; Lachapelle, Philippe; Bowatte, Gayan; Lodge, Caroline; Braitberg, George; Irving, Louis; Hinks, Timothy; Dharmage, Shyamali; Douglass, Jo
Abstract: RATIONALE: On November 21, 2016 in Australia, a major thunderstorm-asthma epidemic struck Melbourne with an unprecedented number of emergency presentations, hospital admissions and fatalities. OBJECTIVES: We identified affected patients who presented to The Royal Melbourne Hospital, an adult tertiary center in North-West Melbourne. We aimed to characterize individual patient factors associated with hospital admission and identify biomarkers in patient subgroups that are at risk of being severely affected by thunderstorm-asthma. METHODS: Cross-sectional, retrospective analysis of demographics of 240 patients presenting to The Royal Melbourne Hospital on November 21 to 22, 2016 post thunderstorm-asthma event and clinical characteristics of 70 of those patients who subsequently attended an outpatient clinic review. RESULTS: Patients were generally young adults (mean age 35 years), with seasonal rhinitis (96%) and universally (100%) sensitized to ryegrass pollen. Forty-four patients (63%) had a known diagnosis of asthma while 20% reported no previous diagnosis but had symptoms consistent with asthma. Patient characteristics associated with hospitalization were: uncontrolled asthma symptoms in the month before the thunderstorm-asthma event, symptomatic allergic rhinitis, high blood eosinophilia and lower lung function. CONCLUSION: Thunderstorm-asthma affects people with seasonal rhinitis, ryegrass sensitization and can occur without prior history of asthma, with dramatic potential to inundate a healthcare system. Our data suggests that hospitalization, and thus a more severe thunderstorm-asthma exacerbation, was associated with a known history of asthma, prior uncontrolled asthma symptoms, allergic rhinitis, high eosinophil count and lower lung function. These factors may inform strategies to identify those most at risk of thunderstorm-asthma.